Integrasi Konsep Teaching Factory Pembuatan Kursi dan Meja dari Daur Ulang Limbah Plastik - Runtuwene, Steven; Slat, Winda Sanni; Rasuh, Adolf Tonny; Hosang, Djefry Paulus; Lambonan, Oldi Malfri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Plastic waste is one of the most urgent environmental problems and continues to increase along with the development of industrial and tourism areas, including in North Minahasa Regency. The high volume of plastic waste generation has not been supported by an adequate management system, resulting in most of the plastic waste polluting the environment. This condition requires innovative solutions to convert plastic waste into valuable products. One approach implemented in this program is the Teaching Factory concept, which integrates learning processes with real production activities. The activities focused on processing plastic waste collected from the community, which was then converted into ready-to-use chair and table products. Through the Teaching Factory approach at the Polimdo campus and partner sites, students and lecturers were directly involved in every stage of production, starting from sorting, shredding, melting, molding, to product assembly. This program successfully collected 47 kg of HDPE, PET, and PP plastic waste, which was then sorted and recycled into plastic sheets, resulting in four chair products and two table products that are ready to use.